Analisis Model Systematic Mapping Study Kepemimpinan dan Komunikasi dalam Meningkatkan Kinerja Pegawai - Hazimah Qatrun Nada Afis; Armida S (Jurnal Ecogen, 2020)
Analysis of leadership and communication on employee performance has the objective to find out what leadership and communication can improve employee performance. The method used in writing this literature review uses the method of systematic literature review (SMS), which is sourced from ecogen sources and some proceedings, it cannot cover all existing journal and conference databases. In addition, we only get categories of articles in Indonesians. With the problem of the past 10 years. Based on 21 literature searches, I found that leadership that can improve employee performance in both goverment agencies and the business and industry world is democratic leadership, as well as communication that can improve employee performance both in goverment agencies and the business and industri world is effective communication both communication vertical, horizontal and diagonal. So democratic leadership and effective communication can improve employee performance both in goverment agencies as well as business and industry. Keywords: leadership, communication, performance